Análise de fibras ópticas baseadas em quase cristais fotônicos - Câmara, João Maria (2014)
In this work, it is analyzed two applications involving optical fiber. In the first application, a new design of an optical fiber coupler composed by two and three cores from a fiber with step index is proposed and analyzed using a vector formulation based on finite element applied in conjunction with genetic algorithm (GA). The fiber is made with pure silica and silica doped with germanium and it is composed by two and three identical cores separated by distance d. The proposed structure has a very simple geometry, and each fiber that composed the coupler is obtained by inclusion of a very small air hole at the core of each conventional step index fibers. Next, optical fiber composed by photonic quasi-crystals, through a quasi-periodic and symmetric matrix, is analyzed using the finite element method, applied in conjunction with perfectly matched layers of type cylindrical. The structure is composed of germanium-doped silica and it is originates from twelve distributions of air holes arranged symmetrically with a defect caused by the absence of central air hole